2022
DOI: 10.3389/fpsyg.2022.1006412
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the knowledge domain of financial decision making: A scientometric and bibliometric study

Abstract: Based on a 12-year bibliographic record collected from the Web of Science (Thomson Reuters) database, the present study aims to provide a macroscopic overview of the knowledge domain in financial decision making (FDM). A scientometric and bibliometric analysis was conducted on the literature published in the field from 2010 to 2021, using the CiteSpace software. The analysis focuses on the co-occurring categories, the geographic distributions, the vital references, the distribution of topics, as well as the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 109 publications
0
1
0
Order By: Relevance
“…In addition to the field of medical health, bibliometrics is also used in the research of intelligent computing, cybernetics and other fields, and has a wide popularity in the process of scientific research activities ( 20 23 ). It is worth mentioning that bibliometrics is also widely used in service network and group decision making ( 24 , 25 ). From our review and analysis of previous literatures, it is found that some scholars have published bibliometric studies only on OA or OP, on the basis of the above, scholars can grasp the relevant studies of OA or OP respectively, and they can have a clear understanding of the separate research focus and hot spot of the two diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the field of medical health, bibliometrics is also used in the research of intelligent computing, cybernetics and other fields, and has a wide popularity in the process of scientific research activities ( 20 23 ). It is worth mentioning that bibliometrics is also widely used in service network and group decision making ( 24 , 25 ). From our review and analysis of previous literatures, it is found that some scholars have published bibliometric studies only on OA or OP, on the basis of the above, scholars can grasp the relevant studies of OA or OP respectively, and they can have a clear understanding of the separate research focus and hot spot of the two diseases.…”
Section: Introductionmentioning
confidence: 99%